FREQUENCY OF HEMODIALYSIS CATHETER RELATED INFECTIOUS COMPLICATIONS IN PATIENTS WITH END STAGE RENAL DISEASE - Uzma Shehzadi (Army Medical College Rawalpindi, 2019)
Objective: To determine frequency of various types of infectious complications occurring in patients undergoing hemodialysis using temporary non-cuffed hemodialysis catheters.